The mineral status of young athletes - Rilova, N.; Troyegubova, N. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
From a physiological point of view, many minerals are of major importance for the high intensity physical activity given their role in the maintenance of muscle contraction, nerve impulse, transport of oxygen, activation of enzymes, immune function, antioxidant activity, bone health, and acid-base balance of blood (Dressendorfer et al., 2002) . The aim of the study is assessment of mineral status in the hair of young athletes. Methods: The content of magnesium, zinc and calcium in the hair samples of 15 young athletes (figure skaters) and 28 healthy children aged 12-16 years was investigated. We used a method of mass spectrometry with inductively coupled plasma mass spectrometer «Elan-9000`, the optical emission spectrometry with inductively coupled plasma optical emission spectrometer for «Optima 2000DV». Results: It was revealed that the level of magnesium, calcium and zinc was significantly lower in the hair of young athletes than in the hair of the control group: magnesium 84,3±4,8 vs. 171,6±3,9 (p<0.05); zinc 158.5±7,2 vs. 204,5±6,4 (p<0.05) (Micheletti, 2001); copper 11,4±0,8 vs. 15,4±0,4(p<0.05). Following the mineral screening, the athletes were given individual advice on the basis of gender, age, micronutrient deficiencies, and physical activity. Repeated hair samples were taken one month after the correction. It was shown that the correction of nutrient intake with mineral supplements led to an significant increase in the mineral content of hair samples. Conclusions: Identified deficit of the minerals in the hair of athletes is probably due to two reasons: the loss of macro-and micronutrients with sweating (Maughan, 2000) and their movement into the intracellular region (in the active muscle cells). Correction changes can lead to better tolerance of stress among athletes who require special endurance (Lukaski, 2001).